Intercropping of root crops with chilli in charlands of Mymensingh (Progressive Agriculture, 2015)
Adoption of intercropping may increases crop production instead of declining trend of agricultural land in Bangladesh. Thus, a field experiment on intercropping of root crops with chilli was executed at char area of Dori Bhabkhali in Mymensingh district during October 2014 to March 2015 to find out an appropriate intercrop for cultivation with chilli for higher productivity and maximum economic return. The experiment was consisted with five crop combinations viz., sole chilli, chilli + radish, chilli+ carrot, chilli + onion and chilli + garlic. Significantly the highest yield (green chilli) was obtained with sole chilli (10.26 t ha-1). Among the intercropping treatments, the highest chilli yield (10.31 tha-1) was obtained from chilli + garlic which were close to chilli + onion whereas the lowest (7.71 tha-1) was found in chilli + radish combination. Intercropping reduced 3 to 48 % chilli yield but total productivity as expressed by chilli equivalent yield increased by 80-135% over sole chilli due to the contribution of companion crops. The highest chilli equivalent yield (25.01 t ha-1), gross return (1250500 Tk ha-1), gross margin (1133500 Tk ha-1) and marginal benefit cost ratio (8.56) were obtained from chilli + garlic combination. Considering the experimental findings, chilli + garlic might be suitable combination for higher productivity and economic return.Progressive Agriculture 26 (2): 109-114, 2015